2017
DOI: 10.1590/0103-8478cr20160721
|View full text |Cite
|
Sign up to set email alerts
|

An overview of Listeria monocytogenes contamination in ready to eat meat, dairy and fishery foods

Abstract: Listeria monocytogenes is a relevant foodborne pathogen in public health, responsible for outbreaks of listeriosis often associated to the consumption of ready to eat meat, dairy and fishery products. Listeriosis is a serious disease that can lead to death and mainly affect children, the elderly and immunocompromised individuals. In pregnant women causes abortion or neonatal listeriosis. In Brazil, ready to eat food are appreciated and increasingly consumed by the population. Furthermore, products such as saus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 36 publications
0
19
1
11
Order By: Relevance
“…A similar trend was observed in the current study with occurrence of 2.4% in meat and 1.3% in seafood. The occurrence of L. monocytogenes in raw meat, milk, and cheese in this study was lower than that found in other countries [4,11,16,[39][40][41][42][43][44][45]. The global L. monocytogenes population diversity in the implicated food vehicles could be attributed to several factors: (i) improvements in detection methodologies, (ii) packing facility, (iii) increases in populations of lactic acid bacteria, yeasts, and molds that might have an impact on the microenvironment supporting growth of L. monocytogenes, (iv) period and temperature degree of the storage condition, (v) handling by the consumers, (vi) unhygienic conditions, (vii) uncontrolled temperature, (viii) glove/hand issues, (ix) environmental (hygienic conditions of the farms, hygienic conditions of the slaughter houses, rodents, workers, the slicer, trash handling, and cleanup operations) contamination and subsequent cross contamination to other products, (x) transport, (xi) in the processing facilities, and (xii) during handling at the outlets.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…A similar trend was observed in the current study with occurrence of 2.4% in meat and 1.3% in seafood. The occurrence of L. monocytogenes in raw meat, milk, and cheese in this study was lower than that found in other countries [4,11,16,[39][40][41][42][43][44][45]. The global L. monocytogenes population diversity in the implicated food vehicles could be attributed to several factors: (i) improvements in detection methodologies, (ii) packing facility, (iii) increases in populations of lactic acid bacteria, yeasts, and molds that might have an impact on the microenvironment supporting growth of L. monocytogenes, (iv) period and temperature degree of the storage condition, (v) handling by the consumers, (vi) unhygienic conditions, (vii) uncontrolled temperature, (viii) glove/hand issues, (ix) environmental (hygienic conditions of the farms, hygienic conditions of the slaughter houses, rodents, workers, the slicer, trash handling, and cleanup operations) contamination and subsequent cross contamination to other products, (x) transport, (xi) in the processing facilities, and (xii) during handling at the outlets.…”
Section: Discussioncontrasting
confidence: 79%
“…Globally, the prevalence rates in fish show great variability [3,25,44,[46][47][48][49]: The prevalence of L. monocytogenes in fish are presumably from contaminated waters or during manipulation and processing with contaminated environment and/or equipment [47,50]. The L. monocytogenes isolated from our frozen fish samples indicates that L. monocytogenes has the ability to endure freezing of food, thereby acting as a reservoir to participate in future human listerial outbreaks [9,25,[51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, L. monocytogenes is a facultatively anaerobic, psychrotroph bacterium (Vázquez-Boland et al, 2001) that grows at refrigerator temperatures, and it is tolerant to low pH and certain preservatives such as sodium chloride, which are inhibitory to other food pathogens (Alves, Martinez, Lavrador, & De Martinis, 2006). L. monocytogenes causes human listeriosis, although rare, has a mortality of 15% to 30% in affected individuals, including pregnant women, newborns, elderly, and immunocompromised people (Rodrigues, Sá, & Melo, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Com o crescimento da produção de suínos no Brasil, órgãos como Ministério da Agricultura, Pecuária e Abastecimento (MAPA) têm focado nos riscos à saúde pública, criando assim Programas de monitoria como o Programa Nacional de Controle de Patógenos (PNCP), monitorando principais patógenos como a Salmonella, Escherichia coli e L. monocytogenes de grande importância à saúde pública. Mesmo com resultado negativo para L. monocytogenes nesta pesquisa, ressalta-se a importância do cumprimento dos procedimentos de autocontrole e prevenção como Procedimentos Padrão de Higiene Operacional (PPHO), Análise de Perigos e Pontos Críticos de Controle (APPCC), Boas Práticas de Fabricação (BPF), bem como a higienização do ambiente de abatedouros-frigoríficos de forma eficiente e rigorosa para que não ocorra a contaminação de produtos e derivados com microrganismos patogênicos e consequentemente infecções alimentares (RODRIGUES et al, 2017). Scallan et al (2011), realizaram um estudo epidemiológico nos Estados Unidos da América com todas as doenças transmitidas por alimentos, durante o período de 2000-2008.…”
Section: Resultsunclassified